2008
DOI: 10.1007/s11064-008-9714-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wnt and PI3K Signaling Modulates GSK-3β Activity and Induces Morphological Changes in Cortical Neurons: Role of Tau Phosphorylation

Abstract: Glycogen synthase kinase GSK-3beta has been identified as one of the major candidates mediating tau hyperphosphorylation at the same sites as those present in tau protein in brain from Alzheimer's disease (AD) patients. However, the signal transduction pathways involved in the abnormal activation of GSK-3beta, have not been completely elucidated. GSK-3beta activity is repressed by the canonical Wnt signaling pathway, but it is also modulated through the PI3K/Akt route. Recent studies have suggested that Wnt si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…Based on our previous studies, the PI3K/AKT pathway is inhibited by Aβ and its recovery by diverse ways is helpful for the prevention of Aβ toxicity [14,15,54]. This finding is also supported by many other researchers [55][56][57]. In other words, Aβ oligomers inhibit the PI3K/AKT pathway and the inhibition of the PI3K/AKT pathway induces neuron death and eventually dementia.…”
Section: The Alteration Of the Pi3k/akt Pathway In Adsupporting
confidence: 58%
“…Based on our previous studies, the PI3K/AKT pathway is inhibited by Aβ and its recovery by diverse ways is helpful for the prevention of Aβ toxicity [14,15,54]. This finding is also supported by many other researchers [55][56][57]. In other words, Aβ oligomers inhibit the PI3K/AKT pathway and the inhibition of the PI3K/AKT pathway induces neuron death and eventually dementia.…”
Section: The Alteration Of the Pi3k/akt Pathway In Adsupporting
confidence: 58%
“…Because inhibition of Wnt signaling by DKK-1 associates with increased GSK-3 activity and tau hyperphosphorylation (Caricasole et al, 2004;Mercado-Gómez et al, 2008;Rosi et al, 2010;SalcedoTello et al, 2014;Scali et al, 2006), we next studied whether this sequence of events would take place in our murine model. In agreement with this line, higher DKK-1 expression observed in the hippocampus of SAMP8 mice was accompanied by an increase in phosphorylated GSK-3a in Tyr 279 (active form), as well as a reduction of phosphorylated GSK-3b in Ser 9 (inactive form) protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] It has also been proposed that insulin can modify microtubule stabilization through inhibition of glycogen synthase kinase 3b (GSK3b), a kinase that can phosphorylate the microtubule-associated protein (MAP) tau. 24,25 Given these crucial roles of insulin in the hippocampus, it could be speculated that systemic insulin alterations resulting from obesity and InsRes could result in hippocampal insulin alterations that underlie cognitive impairment. In this regard, it has been reported that long-term high-fat (not fructose) feeding in mice produced alterations in Akt and GSK3b signaling in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%